2006
DOI: 10.1128/iai.74.1.331-339.2006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CsrC and Characterization of Its Role in Epithelial Cell Invasion in Salmonella enterica Serovar Typhimurium

Abstract: The csr regulatory system of Salmonella regulates the expression of the genes of Salmonella pathogenicity island 1 (SPI1) required for the invasion of epithelial cells. This system consists of the posttranscriptional regulator CsrA and an untranslated regulatory RNA, CsrB, that opposes the action of CsrA. Here we identify and characterize the role of a second regulatory RNA, CsrC, whose ortholog was discovered previously in Escherichia coli. We show that a mutant of csrC has only mild defects in invasion and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
122
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(133 citation statements)
references
References 39 publications
11
122
0
Order By: Relevance
“…UvrY directly binds to the csrB and csrC promoters in vitro (63,73), yet the details of its transcription activation mechanism have not been determined. Though Csr/Rsm-inhibitory sRNAs of various species may bear little sequence identity outside the CsrA/RsmA binding sequences, their expression in most cases is highly dependent on the UvrY ortholog (73)(74)(75)(76)(77)(78)(79). Whether UvrY and its various orthologs have additional regulatory roles remains to be determined, although the GacA protein of P. aeruginosa was proposed only to regulate Rsm sRNA transcription (80).…”
Section: Regulation Of the Csr/rsm Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…UvrY directly binds to the csrB and csrC promoters in vitro (63,73), yet the details of its transcription activation mechanism have not been determined. Though Csr/Rsm-inhibitory sRNAs of various species may bear little sequence identity outside the CsrA/RsmA binding sequences, their expression in most cases is highly dependent on the UvrY ortholog (73)(74)(75)(76)(77)(78)(79). Whether UvrY and its various orthologs have additional regulatory roles remains to be determined, although the GacA protein of P. aeruginosa was proposed only to regulate Rsm sRNA transcription (80).…”
Section: Regulation Of the Csr/rsm Systemmentioning
confidence: 99%
“…Another study identified barA and csrB as regulators of SPI1, which led to further studies on the effects of csrA (271,272). CsrC was identified by its homology with E. coli csrC (77,273). Mutations in barA, sirA, csrB, and csrC all cause decreases in SPI1 gene expression.…”
Section: Salmonella Speciesmentioning
confidence: 99%
“…Regulation of gene expression by CsrAregulated in other species (i.e. Pseudomonas, Erwinia, Salmonella, and Vibrio) is believed to occur in a similar manner as in E. coli (15)(16)(17)(18)(19). The affinity of CsrA for a particular RNA target depends on both the RNA sequence and secondary structure (10,20,21).…”
mentioning
confidence: 99%
“…The ferric uptake regulatory protein, Fur, and the BarA/SirA two-component system are SPI-1 activators (Fortune et al 2006;Ellermeier and Slauch 2008). In turn, HilE (Fahlen et al 2000) and Lon (Takaya et al 2003;Boddicker and Jones 2004) are negative regulators of SPI-1.…”
mentioning
confidence: 99%